Comparative morphology of the compound rhamphotheca of tubenosed seabirds (order Procellariiformes) - Piro, Alejandra (Zoologischer Anzeiger)
Compound rhamphothecae are characteristically present in the order Procellariiformes, but other birds also show this feature: ostriches, tinamous, cormorants, pelicans, herons. In Procellariiformes the shape, size and features of the rhamphotheca are not related to feeding mechanisms and/or displays (as in most birds) but with their nasal gland excretions and highly developed olfactory organ. The compound rhamphothecae are composed by several plates: the dorsal culminicorn, naricorn forming the tubes, the laterals latericorn, and premaxillary nail (upper jaw); the ramicorn and the mandibular nail (lower jaw). A nasolabial groove is present between the culminicorn and the latericorn, and caudally to the premaxillary nail. The mentolabial groove is between the ramicorn and the mandibular nail. Diomedeidae present a pseudomental fold and groove in the ventral part of the mandibular nail, the fold varies in its caudal extension. The ramicorn in Procellariidae is divided longitudinally into ventral and dorsal ramicorn by a suture. This feature is not found in other Procellariiformes except in Phoebetria palpebrata (Diomedeidae). The development and fusion of the tubes in Procellariidae vary as: a single tube, a partially fused tube, or completely separated tubes. Its extension is variable, reaching its greatest length in Macronectes giganteus. In Diomedeidae the configuration of the incurrent and excurrent apertures within or outside the tubes vary, and they present the shortest tubes. The grooves in Procellariidae vary in their development: the nasolabial groove sometimes is well marked with sutures, the ramicorn groove is always a sulcus (except for Fulmarus glacialoides) and expands cranially and/or caudally forming a triangle-shape depending on the species. In Diomedeidae the culminolabial groove presents variation at the dorsal branch, it can be: well developed, less developed or brief. Oceanitidae and Hydrobatidae present less variation. Phylogenetically, beaks of Oceanitidae and Hydrobatidae are the most ...